Smart antioxidant function enhancing (SAFE) nucleic acid therapy for ROS-related chronic diseases and comorbidities - Zhiguo Lu; Ruichen Zhao; Yi Li; Jianze Wang; Jing Guo; Chaobo Bai; Jing Chen; Jun Yang; Yiwan Geng; Tianlu Zhang; Yanyue Wu; Xiyue Jiao; et al. (Bioactive Materials, 2024)
Reactive oxygen species (ROS)-mediated oxidative stress exacerbates chronic diseases such as organ damage and neurodegenerative disorders. The Keap1-Nrf2-ARE pathway is a widely distributed endogenous antioxidant system. However, ROS under redox homeostasis regulates a wide range of life activities. Therefore, smart scavenging of excess ROS under pathological conditions is essential to treat chronic diseases safely. This study reports a smart antioxidant function enhancement (SAFE) strategy. On-demand release of nucleic acid drugs in a pathological ROS environment smartly activates the endogenous antioxidant system, thereby smartly alleviating oxidative stress in an exogenous antioxidant-independent manner. Through structural modulation and ligand modification, we develop SAFE nanoparticles based on nanohybrid complexes (SAFE-complex) adapted to brain delivery of nucleic acid drugs. SAFE-complex with homogeneous monodisperse structure efficiently treat ROS-related neurodegenerative diseases while protecting the major organ from oxidative stress damage. Moreover, SAFE-complex can stabilize storage in the form of freeze-dried powder. These data indicate that SAFE nanoparticles hold promise for treating ROS-related chronic diseases and comorbidities through rational transformation.